Nasal carriage and recurrent pyodermas - Manimala, Anu Cherian; Kurien, George (International Journal of Research in Dermatology, 2017)
Background: Pyodermas are one of the commonest clinical conditions encountered in dermatological practice especially in pediatric practice. Various factors like poverty, malnutrition, overcrowding and poor hygiene have been stated to be responsible for its high incidence. Recurrent pyoderma is another problem encountered by the dermatologist. Nasal carriage of S. aureus has been reported to be an independent risk factor for recurrent pyoderma. The anterior nares are the principal habitat and it has been estimated that some 20% of individuals are persistent nasal carriers; 60-70% are intermittent carriers, about 20% are resistant to nasal colonization. Methods: A study was undertaken to know the common types of pyoderma among patients attending the dermatology OPD in a tertiary care centre in central Kerala. It was also aimed to study the correlation between recurrent pyoderma and nasal carrier state.180patients attending the OPD were studied. They were categorized depending on type of pyoderma. Swabs were taken from the lesions and anterior nares. The results were analyzed using SPSS software. Results: Of the 180 patients studied, 115 had primary pyoderma and 65 had secondary pyoderma. Most common primary pyoderma was impetigo and age group affected was <10 years. 59 patients had recurrent episodes of pyoderma. 43 patients had nasal swab positivity. Of these 43 patients, 30 patients had recurrent pyoderma which is statistically significant. Conclusions: Primary pyodermas are more common than secondary pyodermas and impetigo is still the leading cause of pyoderma. High nasal carriage rates of S. aureus is an independent risk factor for recurrence of pyoderma. Treating the nasal carriage is equally important in the management recurrent pyoderma of the skin.